Corrigendum To ‘‘the Effect of Surface Treatment on Cap Deposition of Ti6al4v Open Cell Foams in Sbf Solution.’’ [ceram. Int. 39 (2010) 1805–1816] - Türkan, Uğur; Güden, Mustafa; Güden, Mustafa (Elsevier Ltd., 2011)
The authors regret that they accidentally omitted to refer to Prof. A.C. Tas, who originally found the SBF solution used in the experiments. The corrections to the affected sentences are listed below. ‘‘The SBF solution for in vitro tests was prepared by dissolving the following analytical reagents in 1 L of deionized water: 6.547 g of NaCl, 2.268 g of NaHCO3, 0.372 g of KCl, 0.124 g of Na2HPO4, 0.305 g of MgCl2 6H2O, 0.368 g of CaCl2 2H2O, 0.071 g of Na2SO4 and 6.057 g of trishydoxmethylaminomethane (A.C. Tas)’’. A.C. Tas, Synthesis of biomimetic Ca-hydroxyapatite powders at 37 8C in synthetic body fluids, Biomaterials 21 (14) (2000) 1429–1438.
Keywords: Surfaces; Apatite; Films; Biomedical applications